RED OCEAN VS BLUE OCEAN STRATEGY: COMPARATIVE ANALYSIS IN CREATING COMPETITIVE ADVANTAGE - Ramlah, Ramlah; Hardianti, Titin; Rahmawati, Rahmawati; Awaluddin, Murtiadi; Sudirman, Sudirman (Journal of Management Small and Medium Enterprises (SMEs), 2026)
In an increasingly competitive business world, companies are required to innovate in order to maintain a competitive advantage. This article aims to analyze the comparison between Red Ocean and Blue Ocean strategies in creating competitive advantage. The research method used is a literature review, by collecting and analyzing related literature from various sources, including scientific journals and research reports. The results of the study indicate that the the Red Ocean Strategy focuses on competition in existing markets, encouraging companies to increase efficiency and product differentiation, but often traps them in price wars. In contrast, Blue Ocean Strategy offers an innovative approach by creating new market space that reduces the intensity of competition, allowing companies to build advantages that are difficult to imitate. Understanding these two strategies is important for determining strategic directions that are in accordance with dynamic market conditions. Keywords: Red Ocean Strategy; Blue Ocean Strategy; Competitive Advantage; Strategic Management